Analysis of Ergonomic Risk Factors with the Incident of Flank Pain in Bank Tellers - Dewi Zuniawati; Poppy Farasari (Indonesian Journal of Global Health Research, 2024)
Office ergonomics is one of the potential causes of pelvic pain which can threaten office workers such as bank tellers. Ergonomic dangers when pelvic pain occurs can come from Work Load, Work Posture, Frequency, Length of Work. Pelvic pain is back pain caused by incorrect ergonomic positions. In this study, researchers wanted to reduce the ergonomic risks experienced by bank teller employees. By reducing ergonomic risks, the health and welfare of employees will improve and can increase work productivity, the company will also improve product quality in the form of services. This research aims to: Analyze ergonomic risk factors with the incidence of flank pain in bank tellers in the X district. Research method: this research uses quantitative descriptive surveys, the sample in this study uses a purposive sampling technique, totaling 30 bank tellers throughout the X District. This research was carried out on January 15 - March 5 2024. The data in this research was obtained by directly observing the results of a walk through survey made in the form of a checklist and analyzed in the form of photos, videos, with a caution zone measuring instrument, then the data that has been collected analyzed using univariate. Results from a walk through survey in the form of a checklist and caution zone assessment, the results of the independent variables are ergonomic risks: Work Load (73.6%), Work Posture (75.6%), frequency (38.1%) and Duration (69.4%) and the dependent variable is the incidence of flank pain (63.1%). Office ergonomics is important to pay attention to because it is one of the potential dangers in the incidence of flank pain, the most dominant factor influencing the incidence of flank pain is the ergonomics factor of incorrect working posture when sitting which will later threaten bank tellers.